Making Up for the Past: How the Oregon Archaeological Society Addresses Its "Collector" Origins. Issue 1 (February 2022) - O'Grady, Patrick; Minick, David L.; Stueber, Daniel O.
Abstract: In 2015, the Oregon Archaeological Society (OAS) presented statements to Oregon tribes and the Oregon Legislative Commission on Indian Services acknowledging the troubling history of OAS collecting activities and steps taken to transform the OAS, and sought guidance to address continuing tribal concerns. Tribes encouraged both the return of collections and increased public outreach efforts. Their guidance fueled increased effort by the Collection Recovery Committee (OASCRC), which has facilitated the return of five collections to tribal museums and university curation facilities and coordinated digital preservation of documents. The OAS may be the only avocational society in the United States actively engaged in such efforts, accomplished by a small group of volunteers. Case studies of collections, considerations involved in disposition, and the potential for repatriation and research are highlighted. The OAS seeks to halt dispersal and commodification of cultural objects and encourage academic research. Quick action can assure that the original collectors or descendants provide key site and location information. Educational opportunities can be rendered to the heritage community, and we are uniquely positioned to contribute to that service.